Enhancing Community Participation in Waste Management Through Waste Banks - I. D. A. A Warmadewanthi; Ary Mazharuddin Shiddiqi; Dian Saptarini; Arvina Anggie Kharizma; Nadia Sephia Audina; Bayu Arnel Premdan Afristo (Universitas Lambung Mangkurat, 2024)
Mojoroto, as the most populated sub-district in Kediri, has a waste generation rate of 0.66 kg/person/day. This sub-district owns 26 waste bank units across 14 urban villages and actively buys and sells waste. The purpose of community service is to innovate in managing waste recycling in Kediri City by utilizing a digital waste recycling application called Apps4SWAM. Changing to a digital system is expected to simplify the waste recycling process and increase system transparency. The actors involved in this activity are customers and waste bank managers. Six active waste banks in the Mojoroto Sub-district participated in this community service activity. The Apps4SWAM application was developed based on input from all stakeholders who use the application. This application was socialized to the community, especially waste bank customers. A survey was also conducted to determine the community's willingness to manage waste and use this application. Two hundred respondents, consisting of waste bank customers and non-waste bank customers, were surveyed about their waste management behaviour and responses to the waste bank application. The results of this activity show that 80% of waste bank managers use this application to facilitate transactions in the waste bank. Customers also stated that the application system makes recording waste easier and faster, making the financial system more transparent. The increase in waste sales after using the app averaged 153%, and the total number of waste bank customers using the app reached 250. However, obstacles are still faced, ensuring all stakeholders involved in recycling in Kediri can fully switch to using the app for waste recycling activities. The government's readiness to continue this program also needs to be considered, while support from other stakeholders such as collectors and industries is also key. This app can potentially form a waste management network, especially in terms of recycling, in Kediri City.